2016
DOI: 10.32728/ric.2016.24/4
|View full text |Cite
|
Sign up to set email alerts
|

Motives and Barriers to the Consumption of Innovative Food Products by Polish and Ukrainian Consumers

Abstract: The significant increase in the number of new food products means consumers have the opportunity to choose from among a wide range of innovative foods, which bring a variety of benefits to consumption, but can also, for some, raise uncertainty, opposition and suspicion. The article reviews the literature on innovative food products and their acceptance by consumers. The results of own research on the purchase motives and barriers to consumption of such products are presented in the context of theoretical consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…davranışların ortaya çıkmasına vesile olmaktadır. Bununla birlikte, yeni yiyecek deneme korkusunun aksine, yeni yiyecek deneme arzusu olan ve bu eğilimi sergileyen kişiler; yeni, farklı ya da garip yiyecekleri arayan ve daha önce denemedikleri ürünleri tercih eden tüketiciler olarak ifade edilebilir (Jasiulewicz & Lemanowicz, 2016). Bu bağlamda; bu kısımda, konu ile alakalı ulusal yayın çeşitlerinden bazıları ile ilgili bilgilerin özetlenmesi yerinde olacaktır.…”
Section: A Li̇teratür Taramasiunclassified
“…davranışların ortaya çıkmasına vesile olmaktadır. Bununla birlikte, yeni yiyecek deneme korkusunun aksine, yeni yiyecek deneme arzusu olan ve bu eğilimi sergileyen kişiler; yeni, farklı ya da garip yiyecekleri arayan ve daha önce denemedikleri ürünleri tercih eden tüketiciler olarak ifade edilebilir (Jasiulewicz & Lemanowicz, 2016). Bu bağlamda; bu kısımda, konu ile alakalı ulusal yayın çeşitlerinden bazıları ile ilgili bilgilerin özetlenmesi yerinde olacaktır.…”
Section: A Li̇teratür Taramasiunclassified
“…According to Van Akkeren and Cavaye (1999), lack of information limits consumers' adoption of a new product since they would not be aware of benefits derived from such innovations as compared to existing solutions. Another study done by Jasiulewicz and Lemanowicz (2016) found that due to consumer rationality, higher prices are a potential barrier to the adoption of new food products innovation. They also found inconvenient packaging, lack of trust in the sustainability claims of new products, and lack of nutritional values, healthiness and taste in the new food products innovation to be the factors limiting their adoption.…”
Section: Introductionmentioning
confidence: 99%